Income versus Non-Income Barriers to Allopathic Health Care: Limits to Subsidies - Mushi, Deograsias (Tanzania Journal for Population studies and Development, 2007)
This paper studies non-income barriers to allopathic health care and considers possible scenarios for subsidy allocation to alleviate the consequent effects on access to public health care. A simple theoretical model is used to derive the effect of non-income barriers to health care and use data from Tanzania to carry out empirical verifications. The results show that access to health care depends on both household income and non-income barriers. Knowledge about the benefits of allopathic health care is crucial in the decision to seek medical care. Information gaps on the benefits of health care system affect choice of providers of medical care. The effect is disproportionately distributed between the least and the relatively more informed households. Also, uniform subsidies in health care tend to favour those with proper knowledge of causes of disease episodes and benefits of allopathic health care. Thus, design of subsidies could reflect the effect of information gaps in order to reduce price sensitivity in charged public health care. However, it might be tedious to compute levels of subsidies by households, but regional indices of information gaps could help to design an effective subsidy scheme in public health care.